The Effectiveness of Attractants for Fruit Fly in Orange Garden (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
Fruit flies are plant-disturbing insects that harm farmers both qualitatively and quantitatively. Initial symptoms of damage to host plants are marked by the appearance of black spots until the plant parts rot and fall. Fruit flies will inject their eggs until they hatch and become larvae, then the larvae will gnaw the fruit flesh from the inside. Control of fruit flies so far still uses factory chemical insecticides that are not environmentally friendly and leave residues that threaten health. Controlling fruit flies that are environmentally friendly and not at risk of leaving residue can use attractants made from natural ingredients. This study was aimed to determine the effectiveness of the use of natural-based attractants that utilize local raw materials on the allure of fruit fly insects. The materials used in this study were clove leaves, lemongrass leaves, guava leaves, pandan leaves, lime leaves, pineapple and star fruit. The tools used to trap insects use two tools, namely trap bottles and glue. The results showed that the use of lemongrass leaves, clove leaves, guava leaves and pineapple fruit was quite effective in trapping fruit fly pests. Lemongrass leaves more effective than others (27 results in a week). A more effective tool to use is fly glue. The most effective combination is glue with clove leaves, guava leaves, and pineapple (number of results is >100 in a week).